Administrative leadership and its relationship to organizational sustainability among secondary school principals from the perspective of physical education teachers in Najaf. - Fahim, L. Dr. Amir; Tuwaij, L. Dr. Karrar Mohammed Mohsen; Hashem, L. Dr. Hussein Ali (Sulaimani Journal for Humanities, 2026)
Administrative leadership is a cornerstone of this development, embracing innovation, change, and improvement. The administrative leadership that drives progress and forms the key to enhancing the quality of work in school administrations reflects the ability of the administrative leader (school principal) to innovate. Today, institutions strive to adopt administrative leadership styles to achieve organizational excellence and ensure its sustainability. Hence the importance of this research, as the understanding of administrative leadership and organizational work among heads of educational institutions strengthens the contribution of teaching staff in secondary schools in Najaf Governorate. This research also aims to explore the relationship between administrative leadership and organizational sustainability from the perspective of physical education teachers. The research concludes by stating that the understanding of administrative leadership and organizational work among heads of educational institutions enhances the contribution of teaching staff in secondary schools in Najaf Governorate. Through the researcher's experience, knowledge, and close contact with secondary school administrations, in addition to interviews conducted with a number of school principals and teachers in this field, it was observed that many educational institutions still lack a clear vision of this concept and how to apply it within their administrations. This is where the research problem lies, as they believe it to be a source of danger that threatens their authority and influence, thus hindering administrative development and organizational change. The aim of the research was to identify the relationship between administrative leadership and organizational sustainability among secondary school principals from the perspective of physical education teachers in Najaf Governorate. The researcher used the descriptive method with a correlational approach due to its suitability to the nature of the current study. The research population consisted of 160 physical education teachers in secondary schools in Najaf Governorate, selected using a comprehensive sampling method. The researchers concluded that there is a simple positive correlation between administrative leadership and organizational sustainability, which significantly contributes to raising the level of administrative leadership among secondary school principals in Najaf Governorate. The researchers recommended that secondary school principals in Najaf Governorate pay attention to administrative leadership and organizational sustainability.